Analysis of Human Resources Readiness in Supporting Energy Transition for National Energy Security - Ardyanto, Fakhriyan; Thamrin, Suyono; Laksmono, Rudy (Indonesian Journal Publisher, 2025)
The transition to renewable energy requires competent human resources (HR) to achieve national energy security. This study examines Indonesia's HR readiness for the energy transition through an integrated perspective on energy security and the defense science philosophy. This systematic literature review analyzed 15 high-quality sources (from 30 initially identified, 2020-2025) to examine human resources readiness for Indonesia's energy transition. Using a PRISMA-aligned methodology, 13 key studies (11 journal articles and two institutional reports) were selected for detailed analysis, with two additional sources supporting the development of the thematic framework. The analysis integrates perspectives on energy security, defense science, and defense anthropology to identify HR readiness challenges, with particular emphasis on regional disparities. Despite Indonesia's renewable energy target of 17%-19% for 2025 (revised from an initial target of 23%), current realization remains at only 13.1% (2024), revealing critical competency gaps in the human resources sector. Key findings include: Indonesia ranks sixth globally for energy-sector emissions (691.97 million tons of CO2 in 2022); significant geographic disparities exist, with Java having 204 educational institutions for energy training, compared to only 3 in remote provinces. Required competencies encompass multidisciplinary technical skills, adaptability to technology, and security-aware soft skills. Policy recommendations include energy security-based training programs, competency certification standards, the establishment of an HR energy security council, and the integration of defense anthropology principles into HR development. This research provides a strategic understanding of HR readiness requirements essential for supporting Indonesia's equitable energy transition toward sustainable national energy security.